Cracking the homologous recombination deficiency code: how to identify responders to PARP inhibitors. (May 2022) - Paulet, Lola; Trecourt, Alexis; Leary, Alexandra; Peron, Julien; Descotes, Françoise; Devouassoux-Shisheboran, Mojgan; Leroy, Karen; You, Benoit; Lopez, Jonathan
Abstract: DNA double-strand breaks are the most critical DNA damage to cells, and their repair is tightly regulated to maintain cellular integrity. Some cancers exhibit homologous recombination deficiency (HRD), a faithful double-strand break repair system, making them more sensitive to poly (ADP ribose) polymerase inhibitors (PARPi). PARPi have shown substantial efficacy in BRCA -mutated ovarian cancer for several years, and their indication has gradually been extended to other tumour locations such as breast, prostate and pancreas. More recently, PARPi were demonstrated to be effective in cancers with an HRD phenotype beyond BRCA mutations. Today, a major challenge is developing tests capable of detecting the HRD phenotype of cancers (HRD tests) and predicting sensitivity to PARPi to select patients likely to benefit from this therapy. This review provides a synthesis of the existing HRD tests, divided into three main approaches to detect HRD: the investigation of the HRD causes, the study of its consequences and the evaluation of the HR activity itself. Highlights: Homologous recombination deficiency (HRD) is targetable by PARP inhibitors. HRD tests are helpful to select patients who may benefit from PARP inhibitors. Genomic scars assays increased the number of patients eligible for PARP inhibitors. Functional tests allow a real-time assessment of homologous recombination activity. Acquired resistances to PARPi have been described and need to be carefully studied.